Environment‐dependent alterations of immune mediators in urban and rural South African children with atopic dermatitis. Issue 2 (15th June 2021) - Lunjani, Nonhlanhla; Tan, Ge; Dreher, Anita; Sokolowska, Milena; Groeger, David; Warwyzniak, Marcin; Altunbulakli, Can; Westermann, Patrick; Basera, Wisdom; Hobane, Lelani; Botha, Maresa; Gray, Claudia; et al.
Abstract: Background: In order to improve targeted therapeutic approaches for children with atopic dermatitis (AD), novel insights into the molecular mechanisms and environmental exposures that differentially contribute to disease phenotypes are required. We wished to identify AD immunological endotypes in South African children from rural and urban environments. Methods: We measured immunological, socio‐economic and environmental factors in healthy children ( n = 74) and children with AD ( n = 78), in rural and urban settings from the same ethno‐linguistic AmaXhosa background in South Africa. Results: Circulating eosinophils, monocytes, TARC, MCP‐4, IL‐16 and allergen‐specific IgE levels were elevated, while IL‐17A and IL‐23 levels were reduced, in children with AD regardless of their location. Independent of AD, children living in a rural environment had the highest levels of TNFα, TNFβ, IL‐1α, IL‐6, IL‐8, IL‐21, MCP‐1, MIP‐1α, MIP‐1β, MDC, sICAM1, sVCAM1, VEGFA, VEGFD and Tie2, suggesting a generalized microinflammation or a pattern of trained immunity without any specific TH polarization. In contrast, IL‐15, IL‐22, Flt1, PIGF and βFGF were highest in urban children. Rural healthy children had the lowest levels of food allergen‐specific IgG4. Early life nutritional factors, medications, animal exposures, indoor environment, sunlight exposure, household size, household income and parental education levels were associated with differences in circulating cytokine levels. Conclusions: This study highlights the immunological impact of environmental exposures and socio‐economic status in the manifestation of immune endotypes in children with AD living in urban and rural areas, which are important in selecting appropriately matched immunological therapies for treatment of AD. Abstract : In this cohort of children with atopic dermatitis from South Africa, elevated TH 2 responses are accompanied by diminished TH 17 responses. Environmental and socio‐economic factors dominate the functional reprogramming of immune cell reactivity in children from urban and rural settings. This data highlights the need to include patients from multiple ethnicities, environments and socio‐economic backgrounds in research studies and clinical trials assessing novel immune targeting therapies.